E-marketing - Strauss, Judy; El-Ansary, Adel; Frost, Raymond; Information Resources Management Association (New Jersey Pearson Education Limited, 2003)
"This reference presents a vital compendium of research detailing the latest case studies, architectures, frameworks, methodologies, and research on e-marketing"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet marketing; Electronic commerce